Multi‐instrument observation of simultaneous polar cap auroras on open and closed magnetic field lines. Issue 4 (28th April 2017) - Reidy, J. A.; Fear, R. C.; Whiter, D. K.; Lanchester, B. S.; Kavanagh, A. J.; Paxton, L. J.; Zhang, Y.; Lester, M.
Abstract: This paper presents observations of polar cap auroral features on 19 January 2008, evaluated using multiple instruments with near‐simultaneous observations in both hemispheres. Analysis of the features indicates that there are at least two formation mechanisms/types of polar cap aurora occurring simultaneously on different magnetic field topologies (one on open and the other on closed magnetospheric field lines). Two high‐latitude structures were observed on opposing sides of the northern hemisphere polar cap in the same time interval. The structure on the duskside was formed on closed field lines that protruded into the polar cap and was generated by the precipitation of electrons with energies varying between 2 and 11 keV consistent with an identified mechanism for the formation of transpolar arcs. However, the structure did not extend fully across to the dayside of the auroral oval but rather stayed at ∼80° magnetic latitude for a minimum duration of 40 min. Thus, this structure is an example of a "failed" transpolar arc. The structure on the dawnside of the polar cap was associated with low‐energy electron precipitation (less than 1 keV) and no associated ion signatures, which is consistent with it being a common low‐intensity arc formed by accelerated polar rain on open field lines. The two separate types of polar cap auroras formed during the same interval, demonstrating the complexity of the solar wind‐magnetosphere coupling during the interval. Key Points: Evidence for two different mechanisms producing aurora in the polar cap occurring simultaneously Example of a polar cap arc formed on closed field lines Example of a polar cap arc formed on open field lines, embedded within polar rain